Faktor – Faktor Yang Mempengaruhi Audit Delay - Dina Puspita Sari; Erly Mulyani (Universitas Negeri Padang, 2019)
This research aims to examine the factors that effect audit delay, loss and profit, size firm, auditor’s opinion, auditor’s reputation. The population in this research are mining companies listed in Indonesia Stock Exchange (IDX) in 2014 to 2017. The sample of study was determined by using purposive sampling method, and that total sample 32 mining companies. The data used is secondary data. The technique of collecting data by documentation at www.idx.co.id. The analytical method used is Moderated Regression Analysis. The result showed loss and profit have negative significant effect on audit delay, size firm have not significant effect on audit delay, auditor’s opinion has negative significant effect on audit delay, and auditor’s reputation have negative significant effect on audit delay.